TrailChain: Traceability of data ownership across blockchain-enabled multiple marketplaces. (July 2022) - Gupta, Pooja; Dedeoglu, Volkan; Kanhere, Salil S.; Jurdak, Raja
Abstract: Today massive amounts of data are generated from Internet-of-Things (IoT) sensors that can be streamed in real-time and utilized for building valuable services. As the demand for data sharing has increased, a new business model of data marketplace has emerged that allows individuals to sell their data to buyers for monetary gain. However, these data marketplaces are prone to various threats such as unauthorized data redistribution/reselling, tampering of data, dishonest data ownership claims, and trade of bogus data. The existing solutions related to data ownership traceability are unable to address the above issues due to ambiguous data ownership, undisclosed data reselling, and dispersal of data ownership across multiple marketplaces. In order to solve the above problems, we propose a novel blockchain framework, TrailChain, that uses watermarking to generate a trusted trade trail for tracking the data ownership spanning across multiple decentralized marketplaces. Our solution includes mechanisms for detecting any unauthorized data reselling within and across marketplaces. We also propose a fair resell payment sharing scheme that ensures the resell revenue is shared with the data owners over authorized reselling. We present a prototype implementation of the system using Ethereum. We perform extensive simulations to demonstrate TrailChain's feasibility by benchmarking performance metrics including execution gas costs, execution time, latency and throughput.